Contestation of state role in ethnoscapes: a contrast between community centrism and dirigisme in Little India governance - Katahenggam, Nagathisen; Balakrishnan, Preveena; Wee, Victor Eng-lye; Kunasekaran, Puvaneswaran; Ragavan, Neethiahnanthan M. Ari (Springer Science and Business Media, 2024)
This paper examines how ethnoscape contests state functions in touristification. It compares a state-led ethnoscape governance model to a community-based, participatory approach. Although cultural tourism is increasingly recognised for its tourism and commercial value, it also serves to build national identity. Little India in Singapore and George Town, Malaysia, have divergent priorities despite their similar roots. Singapore’s Little India combines ethno-tourism with a state-constructed identity. Meanwhile, Little India of George Town is a socio-economic urban space with little official intervention. This brings in the question of the function of the state in contesting the various functions of ethnoscapes. Hence, this study will examine how the state places Indian identity for heritage tourism in Singapore and compare it to George Town. It questions ethnoscape governance with a dirigistic state approach. Then, it examines the challenges of a community-led ethnoscape governance against a dirigistic model. Semi-structured interviews were used to study the stories, experiences, and practices of various stakeholders in both locations using interpretative epistemology to develop relevant themes. Based on the analysis, the rationale for pragmatism in the governance of ethnoscapes Is discussed.